Human Capital and Intellectual Capital in Modern International Business –Based on Studies of the Strategies of Transnational Corporations - Rosińska‑Bukowska, Magdalena (Comparative Economic Research. Central and Eastern Europe, 2019)
The main objective of the article is to discuss the direction of changes in the strategies of the most powerful transnational corporations as a result of adjustments to the new challenges created by the growing role of human capital in contemporary international business. Based on the concept of Grounded Theory Methodology, the author will indicate the main pillars of the strategy which can be considered effective for new challenges. The study has been divided into three parts. The first part discusses the most important theoretical issues concerning the place of human capital in the strategies of contemporary enterprises. In the second part, the author characterizes new trends in international transfers of human capital. In the next part, based on the research, the author discusses the impact of changes on the organizational and management system of enterprises – on the example of the most powerful transnational corporations. The studies have shown that all the most powerful transnational corporations notice the growing role of intellectual capital in contemporary business. The basis of corporations’ strategies is the emphasis put on the development of subsystems of intellectual capital, which refers to the activation of international transfers of human capital. In consequence, the strategies of the development of the most powerful transnational corporations are based on three pillars: networking, orchestration, and coopetition, and they are based on the three subsystems of intellectual capital: organizational capital, innovations, and the institutional environment.